2018
DOI: 10.16984/saufenbilder.332336
|View full text |Cite
|
Sign up to set email alerts
|

Kabiliyet odaklı sanayi kümelenmesi: Sakarya Üniversitesi teknokent örneği

Abstract: Sanayi kümelenmesi, bölgesel kalkınmanın en başarılı araçlarından biri olarak kabul edilmektedir. Bu çalışmanın amacı ise kabiliyet odaklı kümelenme yaklaşımını Sakarya Üniversitesi Teknokent'te yer alan firmaların kabiliyetlerinin ortaya çıkarılması ile ortaya koymaktır. İlk olarak Teknokent'te faaliyet gösteren firmalara anket uygulaması ile firma kabiliyetleri ortaya çıkarılmıştır. Anketler SPSS 18 programı ile değerlendirilmiştir. Anket sonucu elde edilen kabiliyet alanlarına göre derece sıralama ve kümele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It was determined that the individuals living in the village had a higher mean score than the individuals living in the city center and the district. In the study conducted by Özkan with university students in 2018, it was observed that the hometown and place of residence affected the awareness of domestic violence. In the study conducted by Güzel and Camadan with university students, it was determined that the mean scores of students living in the village were higher than those living in the city center (Güzel & Camadan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It was determined that the individuals living in the village had a higher mean score than the individuals living in the city center and the district. In the study conducted by Özkan with university students in 2018, it was observed that the hometown and place of residence affected the awareness of domestic violence. In the study conducted by Güzel and Camadan with university students, it was determined that the mean scores of students living in the village were higher than those living in the city center (Güzel & Camadan, 2021).…”
Section: Discussionmentioning
confidence: 99%